HUBUNGAN ANTARA PENYESUAIAN DIRI DENGAN KENAKALAN REMAJA PADA SISWA SMP NEGERI 1 TELAGA KABUPATEN GORONTALO - anik indarwati; Dian Luawo (Elsia: Jurnal Psikologi Manusia, 2023)
This research aims to determine the relationship between self-adjustment and juvenile delinquency in students of SMP Negeri 1 Telaga. With a quantitative research design approach. Sampling with clustered random sampling technique and a research sample of 71 students. The measuring instrument uses two questionnaires: the self-adjustment questionnaire and juvenile delinquency. The data analysis method uses product-moment correlation. The results of this study show that there is a correlation coefficient value of r = 0.333 with sig ≤ a 0,004 p=0,05, with a sign of moderate relationship closeness and a negative sign in the results that the higher the self-adjustment, the lower the juvenile delinquency.